The 2020 California fire season: A year like no other, a return to the past or a harbinger of the future?. Issue 10 (17th April 2022) - Safford, Hugh D.; Paulson, Alison K.; Steel, Zachary L.; Young, Derek J. N.; Wayman, Rebecca B.
Abstract: Aim: Wildfire burned area, fire size, fire severity and the ecological and socio‐economic impacts of fire have been increasing rapidly in California in recent decades. We summarize the record‐breaking 2020 wildfire season in California statistically, evaluate the drivers of high‐severity burning in the 2020 fires and consider implications for fire and resource management. Location: California, USA. Time period: 2020, with consideration of long‐term trends in many variables. Major taxa studied: Humans, vegetation and wildlife. Methods: We statistically summarize the record‐breaking 2020 fire year in California and outline the salient ecological and socio‐economic impacts. Then we fit two statistical models to determine how a suite of weather‐ and fuel‐related variables influenced high‐severity burning in different vegetation types and in different fire events during the 2020 fire season. Results: In 2020, 1.74 million ha burned in California, 2.2 times more than the previous historical record but only average when compared with pre‐Euroamerican conditions. Economic losses exceeded $19 billion, and 33 people were killed directly by fire. Vegetation type and recent fire history had important effects on burning. Variability in high‐severity burning among vegetation types was driven principally by vapour pressure deficit and wind speed; variability among fire events was related principally to time since the last fire (a surrogate for fuel loading). Main conclusions: The 2020 fires were part of an accelerating decades‐long trend of increasing burned area, fire size, fire severity and socio‐ecological costs in California. In fire‐prone forests, the management emphasis on reducing burned area should be replaced by a focus on reducing the severity of burning and restoring key ecosystem functions after fire. There have been positive developments in California vis‐à‐vis collaborative action and increased pace and scale of fuel management and pre‐ and postfire restoration, but the warming climate and other factors are rapidly constraining our options.